Hyperpolarization of Nitrogen‐15 Schiff Bases by Reversible Exchange Catalysis with para‐Hydrogen. Issue 31 (22nd June 2016) - Logan, Angus W. J.; Theis, Thomas; Colell, Johannes F. P.; Warren, Warren S.; Malcolmson, Steven J.
Abstract: NMR with thermal polarization requires relatively concentrated samples, particularly for nuclei with low abundance and low gyromagnetic ratios, such as 15 N. We expand the substrate scope of SABRE, a recently introduced hyperpolarization method, to allow access to 15 N‐enriched Schiff bases. These substrates show fractional 15 N polarization levels of up to 2 % while having only minimal 1 H enhancements. Abstract : Chemical Schifft : NMR with thermal polarization requires relatively concentrated samples, particularly for nuclei with low abundance and low gyromagnetic ratios, such as 15 N. 15 N Schiff bases (see scheme) have been demonstrated to be a new class of substrates effectively hyperpolarized by Signal Amplification by Reversible Exchange (SABRE).